Variation aware assembly systems for aircraft wings - Vaughan, Dan R.W.; Bakker, Otto Jan; Branson, David T.; Ratchev, Svetan (2016)
Aircraft manufacturers desire to increase production to keep up with anticipated demand. To achieve this, the aerospace industry requires a significant increase in the manufacturing and assembly performance to reach required output levels. This work therefore introduces the Variation Aware Assembly (VAA) concept and identifies its suitability for implementation into aircraft wing assembly processes. The VAA system concept focuses on achieving assemblies towards the nominal dimensions, as opposed to traditional tooling methods that aim to achieve assemblies anywhere within the tolerance band. It enables control of the variation found in Key Characteristics (KC) that will allow for an increase in the assembly quality and product performance. The concept consists of utilizing metrology data from sources both before and during the assembly process, to precisely position parts using motion controllers. In this way the assembly fastening operations can be performed optimally and account for manufacturing induced dimensional variations that reduce cycle times in aircraft wing assembly processes. By alleviating the dimensional variation caused by the upstream manufacturing processes and the inaccuracies in the tooling we will achieve a significant increase in the capability of aircraft wing assembly. To analyze the effectiveness of the VAA system a rib insertion process, occurring in a typical aircraft wing assembly, was replicated on a demonstrator test rig. Industrial grade motion controllers and metrology equipment ware utilized to allow for comparison to current industry practices. The experimental case study is described and initial process data shows promise for future implementation on a full scale assembly system.